Mixed Martial Arts Induces Significant Fatigue and Muscle Damage Up to 24 Hours Post-combat. Issue 6 (June 2019) - Ghoul, Nihel; Tabben, Montassar; Miarka, Bianca; Tourny, Claire; Chamari, Karim; Coquart, Jeremy
Abstract : Abstract: Ghoul, N, Tabben, M, Miarka, B, Tourny, C, Chamari, K, and Coquart, J. Mixed martial arts induces significant fatigue and muscle damage up to 24 hours post-combat. J Strength Cond Res 33(6): 1570–1579, 2019—This study investigates the physiological/physical responses to a simulated mixed martial arts (MMA) competition over 24 hours. Twelve fighters performed a simulated MMA competition, consisting of three 5-minute MMA matches. Physiological/physical data were assessed before (Trest ), directly after round 1 (Trd1 ), round 2 (Trd2 ) and round 3 (Trd3 ), and then 30 minutes (Trecovery30min ) and 24 hours (Trecovery24h ) post competition. Heart rate (HR), rating of perceived exertion (RPE), and blood lactate concentration ([La − ]) were assessed at Trest, Trd1, Trd2, and Trd3 . Biological data were collected at Trest, Trd3, Trecovery30min, and Trecovery24h . Physical tests were performed at Trest, Trecovery30min, and Trecovery24h . HR, RPE, and [La − ] were high during competition. Leukocytes, hemoglobin, total protein, and glycemia were increased at Trd3 compared with all other time points ( p ⩽ 0.05). Cortisol was increased at Trd3 compared with Trest and Trecovery24h ( p ⩽ 0.05). Testosterone was higher at Trd3 and Trecovery30min than Trest ( p < 0.001). Higher values of uric acid were noted during recovery periods ( p < 0.001). Lactate dehydrogenase was lower at Trest compared with Trd3, Trecovery30min, and Trecovery24h ( p ⩽ 0.05). Countermovement jump was higher at Trest than Trecovery30min ( p = 0.020). Consequently, MMA is a high-intensity intermittent combat sport that induces significant fatigue and muscle damage, both of which are still present at 24 hours post competition.